The Issues and Challenges of Small and Medium-Sized Contractors in Adopting Industrialised Building System - Rizal Mohamed, Mohamed; Fadhil Mohammad, Mohammad; Mahbub, Rohana; Adib Ramli, Mohd; Aizat Ahmad Jamal, Khairool (International Journal of Engineering and Technology, 2018)
The construction industry plays an important role in supporting the development of small to medium-sized enterprises (SME) in Malaysia. SME contractors accounted for about 90 per cent while large contractors make up the remaining of only 10 per cent. One of the main issues highlighted by Construction Industry Development Board (CIDB) in Construction Industry Transformation Plan 2016 â€“ 2020 (CITP 2016 â€“ 2020) is regarding SMEs particularly in the issue of the specialisation of SME contractors, especially Bumiputera contractors in the area of Industrialised Building System (IBS) remains low. Thus, an exploratory survey using questionnaires was undertaken with 30 samples of respondents to explore the challenges of SME contractors in adopting IBS in Malaysia. The findings from the study revealed that the low adoption of IBS among SME contractors is due to three (3) main challenges. The main challenges faced by SME contractors in adopting IBS are lack of IBS knowledge, lack of financial backup and clientsâ€™ preference of conventional method over IBS. The findings will be used for the development of a business model framework for SME contractors (not reported in this paper).Â